The Influence of Good Corporate Governance on The Company's Financial Performance - Dwi Septian Zulfizaredo (CV. Syntax Corporation Indonesia, 2024)
This research investigates the impact of Good Corporate Governance (GCG) on the financial performance of property companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2023. Key governance variables include the board of commissioners, board of directors, audit committee, institutional ownership, and managerial ownership. A quantitative associative method was utilized, with data collected from the annual reports of 31 property companies selected via purposive sampling. The analysis was conducted using multiple linear regression with SPSS 25 software. The study reveals that the board of commissioners, board of directors, and audit committee positively and significantly affect financial performance. Conversely, institutional and managerial ownership show a significant negative impact. These findings underscore the importance of effective governance structures in enhancing company performance. Larger boards of commissioners and directors, along with an active audit committee, contribute to better financial outcomes. However, higher levels of institutional and managerial ownership may lead to decisions that negatively affect performance. Good Corporate Governance practices significantly influence the financial performance of property companies. This research provides valuable insights for improving governance frameworks to enhance financial health in the property sector.